Modulation of the expression of an apical plasma membrane protein of Madin-Darby canine kidney epithelial cells: cell-cell interactions control the appearance of a novel intracellular storage compartment (The Rockefeller University Press, 1987)
Experimental conditions that abolish or reduce to a minimum intercellular contacts between Madin-Darby canine kidney epithelial cells result in the appearance of an intracellular storage compartment for apical membrane proteins. Subconfluent culture, incubation in 1-5 microM Ca++, or inclusion of dissociated cells within agarose or collagen gels all caused the intracellular accumulation of a 184-kD apical membrane protein within large (0.5-5 micron) vacuoles, rich in microvilli. Influenza virus hemagglutinin, an apically targeted viral glycoprotein, is concentrated within these structures but the basolateral glycoprotein G of vesicular stomatitis virus and a cellular basolateral 63-kD membrane protein of Madin-Darby canine kidney cells were excluded. This novel epithelial organelle (VAC), which we designate the vacuolar apical compartment, may play an as yet unrecognized role in the biogenesis of the apical plasma membrane during the differentiation of normal epithelia.